PREPARING COMMUNITY RESILIENCE IN SOCIAL SECTOR BASED ON CLIMATE AND DISASTER RESILIENCE INITIATIVE (CDRI) CONCEPT IN SUNGGUMINASA, GOWA REGENCY - Alif Dary Utomo; Risma Handayani (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2021)
The city of Sungguminasa is one of the areas affected by flooding due to the overflow of the Je'neberang River. This is due to urban locations characterized by high population growth and infrastructure as well as land use change around the Je'neberang River. After the flooding, the quality of the settlement environment has decreased, such as damage to the road network and drainage and waste problems. The community is the party most affected by the occurrence of floods, therefore it is very important to increase community resilience in dealing with disasters. Resilience measurement needs to be done to determine the direction of adaptation in accordance with the social conditions of the community in the study site to restore the quality of settlements after the flood disaster. The formulation of the problem in this research is how the social resilience of the community in the recovery of the quality of the post-flood environmental settlements along the River Jeeberang City Sungguminasa. In this study to answer the problem formulation the analytical method used is the Likert scale analysis and analysis of the resilience index value. So the results of the analysis can be concluded that the level of social resilience of the community in the recovery of the quality of the environment after the flooding along the River Jeeberang Sungguminasa City is 4.2 and is in the high category.